TAFSÎR JAMÂ’Î SEBAGAI SARANA MEMADUKAN TEKS DAN KONTEKS ASBÂB AL-NUZÛL - Abdul Rouf (JURNAL AS-SAID, 2023)
The first an Interpreter to notice is the text, because if you don't pay attention to the text, you will certainly get the wrong understanding, and his explanation of the verse will be wrong or make unfounded conclusions. The first step that should not be neglected in the interpretation of the Qur'an is understanding the text. While contextual adherents are groups who really like to do qiyas or analogies. This group prioritizes the meaning of the pronunciation rather than the pronunciation itself. Contextual meaning implies that a word or speech symbol has no meaning if it is separated from the context. Along with the rapid development of technology, the interpreters must be adaptation, dare to make changes in interpreting the verses of the Qur'an with various disciplines, namely with an interdisciplinary and multidisciplinary approach or called tafsr jamâ'î, where the mufasir interprets the Qur'an with an anthropological approach, a sociological approach, a psychological critical discourse analysis approach and a natural or scientific approach. Why? because not all mufasir are figures who master all fields of science, so do scientists who are able to explain various physical and social phenomena, do not have knowledge of interpretation, it is these two groups that are expected to unite because they are considered capable of integrating the text and context of asbâb al-nuzûl. The first an Interpreter to notice is the text, because if you don't pay attention to the text, you will certainly get the wrong understanding, and his explanation of the verse will be wrong or make unfounded conclusions. The first step that should not be neglected in the interpretation of the Qur'an is understanding the text. While contextual adherents are groups who really like to do qiyas or analogies. This group prioritizes the meaning of the pronunciation rather than the pronunciation itself. Contextual meaning implies that a word or speech symbol has no meaning if it is separated from the context. Along with the rapid development of technology, the interpreters must be adaptation, dare to make changes in interpreting the verses of the Qur'an with various disciplines, namely with an interdisciplinary and multidisciplinary approach or called tafsr jamâ'î, where the mufasir interprets the Qur'an with an anthropological approach, a sociological approach, a psychological critical discourse analysis approach and a natural or scientific approach. Why? because not all mufasir are figures who master all fields of science, so do scientists who are able to explain various physical and social phenomena, do not have knowledge of interpretation, it is these two groups that are expected to unite because they are considered capable of integrating the text and context of asbâb al-nuzûl.